2022
DOI: 10.1016/j.bbadis.2022.166340
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of human and murine choroidal neovascularization identifies fibroblast growth factor inducible-14 as phylogenetically conserved mediator of neovascular age-related macular degeneration

Abstract: Background: Visual outcome of patients with neovascular age-related macular degeneration has significantly improved during the last years following the introduction of anti-vascular endothelial growth factor (VEGF) therapy. However, about one third of patients show persistent exudation and decreasing visual acuity despite recurrent anti-VEGF treatment, which implies a role of other, still unknown proangiogenic mediators. Methods: The present study applied transcriptional profiling of human and mouse (C57BL/6J … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…This model has been used to investigate the virology, immunobiology and immunopathology of CHIKV infections (12,14,(24)(25)(26)(27)(28)(29)(30). Given the considerable debate regarding how faithfully mouse models recapitulate the transcriptional responses seen in humans (10,(31)(32)(33)(34)(35)(36)(37)(38), we recently developed a series of bioinformatic methods for investigating how well the transcriptional responses in a given mouse model mimic those seen in humans (39). For human CHIKV patients, RNA-Seq data is available for peripheral blood from acutely infected adults and children (40,41).…”
Section: Introductionmentioning
confidence: 99%
“…This model has been used to investigate the virology, immunobiology and immunopathology of CHIKV infections (12,14,(24)(25)(26)(27)(28)(29)(30). Given the considerable debate regarding how faithfully mouse models recapitulate the transcriptional responses seen in humans (10,(31)(32)(33)(34)(35)(36)(37)(38), we recently developed a series of bioinformatic methods for investigating how well the transcriptional responses in a given mouse model mimic those seen in humans (39). For human CHIKV patients, RNA-Seq data is available for peripheral blood from acutely infected adults and children (40,41).…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing was performed by a commercial provider (GenXPro, Frankfurt am Main, Germany) using massive analysis of cDNA ends (MACE), a 3′-RNA sequencing method, as previously described [ 25 ]. We recently demonstrated that MACE allows sequencing of FFPE samples with high accuracy [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addressing this question, comparing high-resolution human omics data with the molecular profile of the animal model can provide valuable insights when developing novel therapeutic strategies. 100,101 Among the proteomic methods discussed, it is remarkable that liquid biopsies from the vitreous, AH, and even tears can measure proteins originally expressed in the retina. Unexpectedly, these proteins must traverse several anatomic and enzymatic barriers.…”
Section: ■ Challenges and Future Directionsmentioning
confidence: 99%
“…A fundamental question will be which specific molecular aspects of human disease are well reflected by each model. In addressing this question, comparing high-resolution human omics data with the molecular profile of the animal model can provide valuable insights when developing novel therapeutic strategies. , …”
Section: Challenges and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation